Swedish - Finnish glossary: Swedish academic degrees - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary with Swedish academic degrees words. Contains approximately 60 entries. 2013.

Swedish - Finnish glossary with Swedish academic degrees words. Contains approximately 60 words. 2013.

Svensk-sverigefinsk ordlista med svenska akademiska examina. Innehåller ca 60 uppslagsord. 2013
Svensk-finsk ordlista: svenska akademiska examina
Keywords: examinations; examen; academic departments; akademiska institutioner; Academic Dissertation; Akademiska avhandling [Publikationstyp]; word list; ordlista; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur